2001
DOI: 10.1523/jneurosci.21-09-03236.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dopamine in the Nucleus Accumbens and Striatum during Sexual Behavior in the Female Rat

Abstract: Dopamine in dialysate from the nucleus accumbens (NAcc) increases during sexual and feeding behavior and after administration of drugs of abuse, even those that do not directly activate dopaminergic systems (e.g., morphine or nicotine). These findings and others have led to hypotheses that propose that dopamine is rewarding, predicts that reinforcement will occur, or attributes incentive salience. Examining increases in dopamine in NAcc or striatum during sexual behavior in female rats provides a unique situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(126 citation statements)
references
References 22 publications
6
118
1
1
Order By: Relevance
“…Likewise, increasing levels of testosterone and oestrogen promote dopamine release (Hull et al 1999;Auger et al 2001;Becker et al 2001;Appararundaram et al 2002;Creutz & Kritzer 2002;Pfaff 2005). When a male rat is placed in an adjacent cage, where he can see or smell an oestrous female, activity of central dopamine increases and contributes to sexual arousal and pursuit of the female (West et al 1992;Wenkstern et al 1993;Hull et al 1995Hull et al , 1997Hull et al , 2002.…”
Section: The Sex Drive and Mate Preference: Interactionsmentioning
confidence: 99%
“…Likewise, increasing levels of testosterone and oestrogen promote dopamine release (Hull et al 1999;Auger et al 2001;Becker et al 2001;Appararundaram et al 2002;Creutz & Kritzer 2002;Pfaff 2005). When a male rat is placed in an adjacent cage, where he can see or smell an oestrous female, activity of central dopamine increases and contributes to sexual arousal and pursuit of the female (West et al 1992;Wenkstern et al 1993;Hull et al 1995Hull et al , 1997Hull et al , 2002.…”
Section: The Sex Drive and Mate Preference: Interactionsmentioning
confidence: 99%
“…E 2 alters other reward-related processes that increase dopamine release in the nucleus accumbens or striatum of female rats, such as wheel-running, locomotion, and pacing of copulatory contacts (Becker et al, 1987(Becker et al, , 2001; as reviewed by Becker, 1999;Jenkins and Becker, 2003;Mermelstein and Becker, 1995; as reviewed by Lynch et al, 2002;Pfaus et al, 1995;Xiao and Becker, 1997). Pharmacological blockade of estrogen receptors (ERs) in these regions with the selective antagonist, ICI 182,780, but not tamoxifen (which can have both agonistic and antagonistic effects at ERs) attenuates E 2 -facilitated pacing behavior (Xiao and Becker, 1997;Xiao et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…DA release in the striatum, particularly in nucleus accumbens, has been postulated to mediate the reinforcing properties of food, drugs of abuse, and sexual experience. Alternatively, it has been suggested that an increase in extracellular DA in nucleus accumbens or striatum may be associated with stimuli predicting reinforcement (see Becker, Charles, Rudick, William, & Jenkins, 2001). …”
Section: Proestrusmentioning
confidence: 99%